Agility and lean practices as antecedents of supply chain social sustainability. Issue 10 (1st July 2020) - Nath, Vishnu; Agrawal, Rajat
Abstract : Purpose: The present study aims to empirically investigate whether supply chain agility and lean management practices are antecedents of supply chain social sustainability. Design/methodology/approach: Data were collected from 311 supply chain practitioners from the Indian manufacturing sector. Confirmatory factor analysis was employed to test the validity and reliability of the measures used, and a structural model was analyzed to test the hypotheses of the current study. Findings: The results indicate that agility and lean practices are significant antecedents of social sustainability orientation as well as social sustainability performance. The results also suggest that agility has a significant indirect effect on operational performance via social sustainability orientation, basic social sustainability practices as well as agility is indirectly affecting social sustainability performance via social sustainability orientation and basic social sustainability practices. Practical implications: The results of the present study have implications for managers that want to make their supply chain more socially sustainable. Originality/value: The study is unique in the sense that it empirically links agility and lean practices with social sustainability orientation, social substantiality performance and operational performance in supply chains.